Supply Chain Flexibility and Financial Performance "Morocco Case Study" - Lemtaoui Morad; Rochdi Mohamed Houssam (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
Today, and especially in the emergent market, the company success is directly linked to its capacity to deal with the highly changing environment, and how much its supply chain is flexible regarding these changes. The paper analyses how the supply chain flexibility impacts the firms' financial performance in the emergent market, taking Morocco as a study case due to what this country demonstrated as economical resilience during the recent economic crisis and during the "Arab Spring", by applying a multiple linear regression model. The result suggests that the supply chain flexibility has a significant impact on the firms' revenue growth, confirming that today the supply chain flexibility is a key element in the company's business sustainability.
Keywords: 650; supply chain; financial performance; flexibility